Bioceramics in Endodontics: Updates and Future Perspectives - Dong, Xu; Xu, Xin (Bioengineering (Basel), 2023)
Bioceramics, with excellent bioactivity and biocompatibility, have been widely used in dentistry, particularly in endodontics. Mineral trioxide aggregate (MTA) is the most widely used bioceramic in endodontics. Recently, many new bioceramics have been developed, showing good potential for the treatment of endodontic diseases. This paper reviews the characteristics of bioceramics and their applications in various clinical endodontic situations, including root-end filling, root canal therapy, vital pulp therapy, apexification/regenerative endodontic treatment, perforation repair, and root defect repair. Relevant literature published from 1993 to 2023 was searched by keywords in PubMed and Web of Science. Current evidence supports the predictable outcome of MTA in the treatment of endodontic diseases. Although novel bioceramics such as Biodentine, EndoSequence, and calcium-enriched mixtures have shown promising clinical outcomes, more well-controlled clinical trials are still needed to provide high-level evidence for their application in endodontics. In addition, to better tackle the clinical challenges in endodontics, efforts are needed to improve the bioactivity of bioceramics, particularly to enhance their antimicrobial activity and mechanical properties and reduce their setting time and solubility.